Military food engineering and ration technology - Barrett, Ann H.; Cardello, Armand V. (DEStech, 2012)
Written by a team from the U.S. Army's Combat Feeding Directorate at the Natick Research, Development and Engineering Center, this technical volume represents a comprehensive guide to how the military designs, processes, customizes, packages and distributes highly palatable, long shelf-life food products for field personnel. The book offers new data on numerous technologies used to solve problems such as nutrient densification, lightweighting, novel thermal processing, and long-term quality preservation in delivering appetizing foods. Testing techniques are explained for evaluating sensory qualities of foods and their effects on physical and cognitive performance.